Hemodynamic monitoring and outcome-A physiological appraisal - Chan, Y.K.; Khan, Z.H (Elsevier, 2011)
Hemodynamic monitoring provides us with refined details about the cardiovascular system. In spite of increased availability of the monitoring process and monitoring equipment, hemodynamic monitoring has not significantly improved survival outcome. Care providers should be cognizant of the role of the cardiovascular system and its importance in oxygen delivery to the cells in order to sustain life. Effective hemodynamic monitoring should be able to delineate how well the system is performing in carrying out this role. Different hemodynamic monitors serve in this role to a different extent; some provide very little information on this. The cardiovascular system is only one of the many systems that need to function optimally for survival; others of equal importance include the integrity of the airway, the breathing process, the adequacy of hemoglobin level, and the health of the tissue bed, especially in the brain and the heart. Advances in hemodynamic monitoring with focus on oxygen delivery at the cellular level may ultimately provide the edge to effective monitoring that can impact outcome.